2016
DOI: 10.18632/oncotarget.7149
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-FLIPL expression by miRNA-708 increases the sensitivity of renal cancer cells to anti-cancer drugs

Abstract: Dysregulation of the anti-apoptotic protein, cellular FLICE-like inhibitory protein (c-FLIP), has been associated with tumorigenesis and chemoresistance in various human cancers. Therefore, c-FLIP is an excellent target for therapeutic intervention. MicroRNAs (miRNAs) are small non-coding RNAs that are involved in tumorigenesis, tumor suppression, and resistance or sensitivity to anti-cancer drugs. However, whether miRNAs can suppress c-FLIPL expression in cancer cells is unclear. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 40 publications
(38 reference statements)
1
37
0
Order By: Relevance
“…We found that reexpression of miR‐708 significantly reduced the IC 50 values for cisplatin in parental and cisplatin‐resistant ovarian cancer cell lines. In line with our findings, it was reported that ectopic expression of miRNA‐708 increased the sensitivity of renal cancer cells to anti‐cancer drugs (Kim et al, ). Taken together, our data suggest that miR‐708 downregulation contributes to the acquisition of cisplatin resistance in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…We found that reexpression of miR‐708 significantly reduced the IC 50 values for cisplatin in parental and cisplatin‐resistant ovarian cancer cell lines. In line with our findings, it was reported that ectopic expression of miRNA‐708 increased the sensitivity of renal cancer cells to anti‐cancer drugs (Kim et al, ). Taken together, our data suggest that miR‐708 downregulation contributes to the acquisition of cisplatin resistance in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…We did not observe a correlation between the number of potential target genes for a miRNA and the number of cohorts where it is predicted ( Figure S20). All these miRNAs are derived from precursors of already established oncomiRs or tumor suppressor miRNAs, or known to be involved in immune response or inflammation [50][51][52][53][54][55][56][57][58][59][60][61]. Note that hsa-miR-17-3p, hsa-miR-17-5p, hsa-miR-18a-3p, hsa-miR-18a-3p, hsa-miR-20a-3p, hsa-miR-20a-5p, and hsa-miR-92a-1-5p are part of a single miRNA cluster on chromosome 13 and this polycistronic cluster (known as miR-17-92) is well known to be composed of oncomiRs involved in proliferation and tumor angiogenesis, and reducing apoptosis of cancer cells [50].…”
Section: Combining Transcriptional and Post-transcriptional Regulatiomentioning
confidence: 99%
“…In renal cell carcinoma (RCC), miR-708-5p suppresses tumorigenicity by targeting multiple pro-survival genes [ 175 , 176 ]. It was revealed that miR-708-5p has reduced expression in RCC tumor samples, and low expression is associated with advanced tumors [ 175 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that miR-708-5p has reduced expression in RCC tumor samples, and low expression is associated with advanced tumors [ 175 ]. miR-708-5p restoration resulted in decreased cell viability, migration, invasion, and proliferation while also inducing apoptosis in RCC cell lines [ 175 , 176 ]. miR-708-5p treatment in xenograft rodent models reduced tumor burden and synergistically suppressed tumor growth when used in combination with the chemotherapeutic doxorubicin [ 175 , 176 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation